FAMILY MORAL IDEAS AND ACTIONS AS THE DECISIVE FACTOR OF QUALITY EDUCATION IN THE CONTEXT OF SCHOOL – FAMILY – COMMUNITY PARTNERSHIP - CUZNEȚOV, Larisa (Acta et Commentationes, Sciences of Education, 2019)
The article is a theoretical and applicative study related to the essence, conditions and content of the school-family-community collaboration by analyzing the involvement of the family as an actor and decisive factor in achieving a quality education within the social and educational partnership. It is analyzed and established the specificity and influence of family moral ideas and actions on increasing the efficiency of collaboration within the school partnership - family - community, addressed from the perspective of the three postfigurative, cofigurative and prefigurative cultures (representing the three human generations).